STATE AND OUTLOOK OF A SURGICAL SERVICE IN IVANO-FRANKIVSK REGION - Шевчук, М. Г.; Пилипчук, В. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Is reviewed activity of a surgical service of region for 2005 in matching with analogical parameters for the previous years. Is shown the qualifying characteristic of the surgeons, parameters of certification. It was analysed the out-patient help, activity of surgical hospitals of area behind miscellaneous nosological units scheduled and emergency surgery. The attention on the detected lacks is stressed and it is planned pathes for their liquidation.